Antiseptic Effect of Conventional Povidone–Iodine Scrub, Chlorhexidine Scrub, and Waterless Hand Rub in a Surgical Room: A Randomized Controlled Trial. (20th December 2016) - Tsai, Jui-Chen; Lin, Yen-Kuang; Huang, Yen-Jung; Loh, El-Wui; Wen, Hsiao-Yun; Wang, Chia-Hui; Tsai, Yin-Tai; Hsieh, Wen-Shyang; Tam, Ka-Wai
Abstract : OBJECTIVE: Effective perioperative hand antisepsis is crucial for the safety of patients and medical staff in surgical rooms. The antimicrobial effectiveness of different antiseptic methods, including conventional hand scrubs and waterless hand rubs, has not been well evaluated. DESIGN, SETTING, AND PARTICIPANTS: A randomized controlled trial was conducted to investigate the effectiveness of the 3 antiseptic methods among surgical staff of Taipei Medical University—Shuang Ho Hospital. For each method used, a group of 80 participants was enrolled. INTERVENTION: Surgical hand cleansing with conventional 10% povidone–iodine scrub, conventional 4% chlorhexidine scrub, or waterless hand rub (1% chlorhexidine gluconate and 61% ethyl alcohol). RESULTS: Colony-forming unit (CFU) counts were collected using the hand imprinting method before and after disinfection and after surgery. After surgical hand disinfection, the mean CFU counts of the conventional chlorhexidine (0.5±0.2, P<0.01) and waterless hand rub groups (1.4±0.7, P<0.05) were significantly lower than that of the conventional povidone group (4.3±1.3). No significant difference was observed in the mean CFU count among the groups after surgery. Similar results were obtained when preexisting differences before disinfection were considered in the analysis of covariance. Furthermore, multivariate regression indicated that the antiseptic method ( P =.0036), but not other variables, predicted the mean CFU count. CONCLUSIONS: Conventional chlorhexidine scrub and waterless hand rub were superior to a conventional povidone–iodine product in bacterial inhibition. We recommend using conventional chlorhexidine scrub as a standard method for perioperative hand antisepsis. Waterless hand rub may be used if the higher cost is affordable. Infect Control Hosp Epidemiol 2017;38:417–422